The Amazon region at the heart of the Brazilian economys commodity-export model: The case of the State of Pará - United Nations Economic Commission for Latin America; the Caribbean (CEPAL Review, 2024)
The Brazilian economy has undergone far-reaching changes, related especially to the loss of industrial capacity as deindustrialization has spread and commodity-export production has expanded. The Brazilian Amazon region forms part of the expansionary logic of the agro-industry and mining sectors. This article analyses the economic reproduction model of one of the main federative units located in that region, the State of Pará. It uses the specialization coefficients and location quotients of Brazil’s 27 subnational federative units, to make a case study of that State. The findings reveal a declining industrial structure, particularly in manufacturing industry, accompanied by growth in the mining and metallurgical sector. Economic activity has become increasingly concentrated in the production of raw materials and semi-finished industrial inputs, of low technological content.